PENGARUH LATIHAN ASERTIF TERHADAP KEMAMPUAN MENGENDALIKAN MARAH PADA PASIEN PERILAKU KEKERASAN DI PUSKESMAS REJOSO KABUPATEN NGANJUK - wahyudi, Heru; Wilda, Lexy Oktora; Putri, Alfimay Natysya (JURNAL SABHANGA, 2023)
Efforts to control anger in violence behavior generally still use restraints. However, the effort to control anger that is often used by health workers in Mental Hospitals as an intervention for mental disorders patients with violence behavior because it is proven to have a significant effect in controlling anger in these patients is assertive exercise. The purpose of this study was to determine the effect of assertive training on the ability controlling anger in violence behavior patient at Rejoso Health Center in Nganjuk District